-3(6y-4)-y=-3(y-2)

Simple and best practice solution for -3(6y-4)-y=-3(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6y-4)-y=-3(y-2) equation:



-3(6y-4)-y=-3(y-2)
We move all terms to the left:
-3(6y-4)-y-(-3(y-2))=0
We add all the numbers together, and all the variables
-1y-3(6y-4)-(-3(y-2))=0
We multiply parentheses
-1y-18y-(-3(y-2))+12=0
We calculate terms in parentheses: -(-3(y-2)), so:
-3(y-2)
We multiply parentheses
-3y+6
Back to the equation:
-(-3y+6)
We add all the numbers together, and all the variables
-19y-(-3y+6)+12=0
We get rid of parentheses
-19y+3y-6+12=0
We add all the numbers together, and all the variables
-16y+6=0
We move all terms containing y to the left, all other terms to the right
-16y=-6
y=-6/-16
y=3/8

See similar equations:

| 4z+12=22+2z | | 2/5=2x-3/4x-5 | | -3(2-r)=12 | | 855=(x+18) | | 2x(-3+4x)=39 | | 4+7x=7(x-1) | | 7x-35=4x+7 | | 12x2-7x+12=0 | | 8-(-7-8x)=31 | | 21/2w=63/4 | | 22x-19=20-33x | | 7w=10+2w | | 1x+2-1=1x+2 | | 5f+2=28 | | e/5-36=30+4 | | 32=(1/2)(3)(x^2 | | h=400-16*3^2 | | 32=(1/2)(3)(x2) | | -18-k=3k-6(8k+3) | | x+60+63=180 | | 1+14x=13x+13 | | -71=x➗64 | | (n)=1+(4-1)(-4.1) | | (2m/5)=(1/3)(2m-12) | | (n)=1+(10-1)(-4.1) | | -19-17=6x+3(-4-6x) | | 4/5x5+7/5=4 | | 8r+34=114 | | 1/2x-3=4/5x+1 | | 55x+10=50 | | 3(x-1=12 | | 3x-11x=21+x-15 |

Equations solver categories